2019
DOI: 10.1186/s12957-019-1718-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting recurrence after curative resection for rectal cancer: a 16-year study

Abstract: BackgroundThe recurrence after curative surgery of the rectal adenocarcinoma is a serious complication, considered as a failure of the therapeutic strategy. The aim of this study was to identify the different prognostic factors affecting the recurrence of adenocarcinoma of the rectum.MethodsA retrospective analysis of patients operated for adenocarcinoma of the rectum between January 2000 and December 2015 was conducted. The study of the recurrence rate and prognostic factors was performed through the Kaplan M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 30 publications
(38 reference statements)
0
32
0
1
Order By: Relevance
“…One of the most important risk factors for local recurrence is the severity of disease at the time of an initial operations [ 26 , 27 ]. Over half of patients with p/ypT4N2 in our series did not have local recurrence after primary tumor treatment (42.9%).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important risk factors for local recurrence is the severity of disease at the time of an initial operations [ 26 , 27 ]. Over half of patients with p/ypT4N2 in our series did not have local recurrence after primary tumor treatment (42.9%).…”
Section: Discussionmentioning
confidence: 99%
“…None of them individually has provided reliable prognostic utility and there is a paucity of data investigating the effect of regional location on possible risk factors. Some of the variables correlated with higher risk of recurrence include a distal margin <2 cm, lymph node involvement, tumour stenosis, lymphovascular invasion and higher stage 5,6 . Other factors such as perforation and uncertain or non‐radical surgical procedures have been flagged as significant predictors for local recurrence 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, colorectal LRs are localized outside the anastomosis [ 22 25 ], which may suggest a use for diagnosis imaging method, such as CT colonography [ 23 ]. Fuccio et al [ 26 ] showed in the meta-analysis that the incidence of intraluminal LR in rectal cancer is 2 times higher than that in colon cancer.…”
Section: Discussionmentioning
confidence: 99%